The Clinic of Identifications in the Different Processes of Metamorphosis Into Woman - Westphal, Laure; Lamote, Thierry (Frontiers in Psychology, 2018)
This article examines, from a psychoanalytical perspective, the function of identification in the relationship between the subject of the unconscious and his body, his body image, and the other. To this effect, it leans on the clinic of the metamorphosis into woman in psychosis, both in the way that it is presented by patients in the context of treatment and in the form of testimonies extracted from literature. It demonstrates how specular identification allows the subject to unify himself, so long as there is an avoidance of possible deformations of the psychical body, including for example the delusion of transforming into a woman. It also turns its attention to the second logical moment of identification, when identification becomes sexed and organizes a certain relation to the other. A failure in this process sometimes leads the subject to opt for an identification of a gendered look, so as to stabilize himself. Transsexualism, which is not the privilege of neurosis, can be conceived of by the psychotic subject as a welcome way of problematizing his relation to the body and to the other by identification with the woman, now that progress in science and law have enabled this.